ANALISIS PELAKSANAAN TUGAS DAN FUNGSI BNN DALAM MENANGGULANGI PENYALAHGUNAAN NARKOBA PADA PESERTA DIDIK DI KOTA PEKANBARU - Wirasa, Muhammad Arief; Hambali, Hambali; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The background of this study is the increasing number of students who abuse drugs in Indonesia especially in the Pekanbaru city. According tribun Pekanbaru newspaper on 23 January 2015, many as 409 students in the Pekanbaru were involved drug abuse. Therefore, it takes effort from the BNN Pekanbaru to protect learners from the dangers of drug abuse. This study is aimed to find out how BNN Pekanbaru perform its dutties and address drug abuse. The informant in this study were the board directors of BNN Pekanbaru. The Instrument of the data were collected throught observation, interviews and documentation. The data were analyzed by using descriptive qualitative and researchers data analysis techniques use data reduction, data presentation and conclusion. BNN Pekanbaru in carrying out its duties and functions on tackle drug abuse in students applied various programs with priority and non-priority scales. The priority scale includes cooperation with hospitals to carry out rehabilitation and sosialization of P4GN in schools and community components in Pekanbaru city. Then fore the non-priority program, BNN Pekanbaru conducted the dangers of drugs throught posters, banners, billboards and invites schools to form anti-drug task forces in school that were represented by the students. In the performance of dutties and functions, BNN Pekanbaru experiences several impediment and obstacle as shortage of members BNN Pekanbaru and the very limited participation of society. However, the matter is not a significant obstacle to BNN Pekanbaru in the duties and function.Key Words : Implementation Duties and Function of BNN, Drug, Student